Normative data of the start in the 50 m events at the 2021 LEN European Championships and understanding its relationship with the final race - Morais, J. (European Journal of Human Movement, 2022)
This study aimed to: (i) present normative data of the variables related to the start in the four swim strokes by tier and sex, and; (ii) understand the relationship between the 15th meter mark time and the final race time of the male and female swimmers competing in the four 50 m events at the 2021 European Championships. Participants were all male and female swimmers who competed in the 50 m events at the 2021 LEN European Championships held in Budapest. The official race times and block times were retrieved from the official competition website. All starting variables were analyzed in a dedicated software for race analysis. The 15th meter mark time was used as the start main outcome. For all events by sex, the 15th meter mark time was the variable presenting the highest and largest tier effect (p < 0.001) besides the final race time. Overall, despite the swim stroke, the variables related to the underwater phase were also responsible for the significant tier effect (p < 0.001). The 15th meter mark time presented a high to very-high relationship with the final race time in all four swim strokes. This relationship was stronger in freestyle (both sexes). That is, swimmers who achieve the 15th meter mark sooner are more likely to deliver better performances. Coaches must be aware that the underwater phase plays a key-role on the swimmers` (both sexes) start performance. Nonetheless, different strategies can be used based on the swimmers` strength and weaknesses. Moreover, the start performance in all four swim strokes and in both sexes can strongly predict the final race time.